Dental morphology and gingival zenith in teenagers from Junin region - García, Sixto (2021)
Aesthetics in dentistry has gained greater importance, various anthropometric studies of aesthetics parameters have been developed, but these were developed in Caucasian populations. Objective: to determine the relationship of the gingival zenith and the dental morphology of the maxillary teeth of the anterior sector in Peruvian adolescents. Material and Methods: The study was descriptive, correlational and cross-sectional. The sample was of the probabilistic type for convenience, and consisted of 92 adolescents in the Junín region, Peru. Each model was analyzed and the dental morphology, the position of the gingival zenith and the distance from the gingival zenith to the longitudinal axis of the tooth were recorded. Results: The study obtained that the mean location of the gingival zenith for the upper central incisor was 72.8% distally (0.54 mm), for lateral incisor was 59.2%  and for upper canine was 50.5 %, located in the same position as the longitudinal axis of the tooth. Regarding the type of dental shape, the oval shape was found in 71.2% of upper central incisors, in 67.9% of upper lateral incisors and in 73.9% of the canines. Location of gingival zenith in the upper central incisors was distal in relation to the longitudinal axis, with an average distance of 0.54 mm, whereas in upper lateral incisors and upper canines, their gingival zenith was on tooth longitudinal axis. About dental morphology, oval shape was the most predominant. Conclusions: There is a distal migration of gingival zenith in the central incisors, but not in the lateral incisors or upper canines.